Konseling Adlerian Dalam Perspektif Multibudaya - Bakhrudin All Habsy; Tazkia Aulia Az-Zahra; Dira Anindia Ayu Rosidin; Wardah Rikza Firdaus (Pusat Riset dan Inovasi Nasional, 2024)
Adlerian counseling is a counseling approach that refers to individuals who want to achieve their life goals by motivating them towards mastery and fulfillment of life needs, Adler also considers that social interest is a measure of mental health. In the Adlerian counseling process, multicultural competence is considered very important as a form of empathy that can be shown by counselors to individuals with the same cultural background. This research method is skinative with a type of literature study, literature study is a technique or method by reviewing sources that have been made before, such as collecting library data, reading, recording, and reprocessing materials that will be used for research. The purpose of the research is to discuss Adlerian counseling in a multicultural perspective. The results of this study include (1) Adlerian counseling there are several techniques that can be used including interpretation, dream analysis, and also free association. (2) Adlerian counseling has stages that are important to do, namely developing relationships, exploring the dynamics of individual psychology, and finally encouraging self understanding and insight. (3) Adlerian counseling has advantages and disadvantages, which can be adjusted to the problems of the counselee that must be resolved. (4) Adlerian counseling often uses a multicultural perspective where the counseling process must run by adjusting the culture between the counselor and the counselee in order to establish a deep relationship and empathy based on similar cultural backgrounds.